Memorandum of understanding between Universiti Teknologi MARA and Teknik Janakuasa Sdn Bhd / Fakulti Kejuruteraan Elektrik - Universiti Teknologi MARA, Fakulti Kejuruteraan Elektrik (Universiti Teknologi MARA (UiTM), 2019)
Teknik Janakuasa Sdn Bhd (TJSB), a wholly-owned subsidiary of Malakoff Corporation Bhd (Malakoff), a member of MMC Group, signed a Memorandum of Understanding with the Centre for Power Electrical Engineering Studies (CEPES) of the Universiti Teknologi MARA's (UiTM) Engineering Faculty for future collaborations on research and innovation, industrial training and other relevant academic activities. The ceremony took place at the Faculty of Engineering, UiTM Shah Alam campus.